A framework for crew scheduling management system using multi-agents system - Shibghatullah, Abdul Samad; Eldabi, Tillal; Rzevski, George (2006)
Bus crew scheduling problem is a complex problem to solve because of the large number of resources that need to be managed, complexity of allocating crew shifts, rising cast of crew and unpredictability of traffic and crew availability. This causes a difficulty to maintain an optimal schedule. Existing systems are excellent in producing optimal or near optimal schedules. However, to maintain such optimality for day-to~day operations, crew scheduling systems need to extend their capabilities by enabling crew re-assignment, a feature that is not currently available in automated scheduling systems. This paper ﬁrst, presents the role of supervisor in managing unpredictable events then proposes a conceptual framework for developing a crew schedule management system, aiming at maintaining smooth operations of existing crew schedules. The paper also discusses the use of Multi Agents System (MAS) as a suitable approach to implement the proposed concepts.